Palaeogeographic and tectonic setting of the Lower Jurassic (Pliensbachian‐Toarcian) Nishinakayama Formation, Toyora Group, SW Japan. (11th February 2019) - Izumi, Kentaro; Suzuki, Kazue; Kemp, David B.; Iizuka, Tsuyoshi
Abstract : The palaeogeographic and tectonic setting of the Lower Jurassic Nishinakayama Formation (Toyora Group, southwest Japan) is interpreted based on new U–Pb ages for detrital zircon grains separated from a sandstone sample, combined with available provenance data. The newly obtained age spectrum of detrital zircon grains is characterized by multiple age clusters. Specifically, (1) nearly syndepositional (Lower Jurassic; 182–200 Ma), (2) Early Permian to Late Triassic (205–288 Ma), and (3) Precambrian (1, 855–2, 660 Ma). The youngest zircon age (182.4 ± 5.1 Ma) is consistent with the biostratigraphically constrained depositional age ( falciferum ammonite Zone, lower Toarcian). The presence of a near‐syndepositional age cluster, as well as the presence of volcanic tuff layers in the studied succession, indicates the likely extensive influence of an active volcanic arc in the depositional area. The age cluster of 205–288 Ma suggests, in contrast, that older granitic batholiths were also being sourced. Precambrian detrital zircon grains would have been derived from continental blocks with mainly Proterozoic crusts, most likely from the North China Craton. When combined with available geochemical, petrological, and palaeontological data, our detrital zircon data demonstrate that deposition of the Nishinakayama Formation was located at an active continental margin, possibly close to the northern extremity of the South China Craton. Abundant terrigenous clastics were likely supplied to the sedimentary basin from the Qinling‐Dabieshan‐Sulu Suture Zone, which was formed by the collision of the North and South China cratons.